(untitled) (The Pakistan Development Review, 2016)
President Pakistan Society of Development Economists (PSDE) and Vice Chancellor of Pakistan Institute of Development Economics (PIDE) Dr Asad Zaman, Secretary Planning, Secretary PSDE, distinguished economists, eminent scholars from overseas, and young economists of Pakistan. Ladies and gentlemen, it is indeed a great honour and privilege for me to be the chief guest at the opening ceremony of the 31st Annual General Meeting and Conference of Pakistan Society of Development Economists. I happen to be a teacher as well as the politician, so, I promise you to be succinct while inaugurating the Conference. It is a matter of great pride to acknowledge that the tradition initiated by the Society in 1982 continues with great strength. All credit goes to Prof. Nawab Haider Naqvi, one of the founding fathers of this tradition. It is also a tribute to the sincerity of those who are keeping this tradition alive. I hope this tradition of knowledge sharing and intellectual debate will be of practical benefit to the development journey of Pakistan. I am sure that it will go on uninterrupted in future as well, and through such platforms we will be getting new ideas and solutions to our problems. Allama Iqbal also penned down such thoughts: